ESENSI INTEGRITAS DALAM KEPEMIMPINAN BERKARAKTER DISEKOLAH - Farzana, Nurin; Hidayati, Nurul; Mahdum, Mahdum; Azhar, Fadly; Dahnilsyah, Dahnilsyah (STKIP Pesisir Selatan, 2025)
Objective: This study aims to explore the essence of integrity in character-based leadership in schools through contemporary national and international literature reviews. The main focus is understanding how the concept of integrity is explained in educational leadership literature and how integrity shapes effective character-based leadership practices in schools. Methods: The research employs a narrative literature review approach by analyzing articles from SINTA, Scopus, DOAJ, ERIC, and Google Scholar databases published between 2020-2025. Selection criteria include topics on integrity in educational leadership, ethical leadership, and character leadership with focus on their influence on teacher performance and school environment. Results: Findings indicate that integrity is a core value that stands independently in educational leadership, encompassing dimensions of honesty, fairness, transparency, and moral consistency. Integrity shapes effective leadership practices through four pathways: fairness and moral consistency, moral exemplary, building trust, and creating a positive school culture. Cross-country studies prove that principal integrity significantly influences teacher trust, work motivation, organizational citizenship behavior, and overall school quality.